Insertion of Hungarian Tsigai into the sheep of Europe according to maternal origin (mtDNA CR) - Annus, Kata; Kovács, Endre; Sáfár, László (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The Hungarian Tsigai is an old traditional sheep breed. On the course of preservation of the rare domestic animal breeds the maintenance of a greater genetic diversity is essential. In this recent study we analysed first the genetic background in this sheep breed by the use of mitochondrial DNA (mtDNA) sequence, and compared it to the sequences of GenBank. The investigation was also carried out in order to serve data for a sustainable within family selection. The blood samples were taken from the descendants of the so called eldest families based on the herd book (and from two more breed variants, altogether from 81 individuals) in 2014. The control region of mtDNA showed nucleotide deviation at 98 sites. However, the differences among the individuals were limited to few loci; so the maternal genetic background of the Tsigai breed seems to be unified. The genetic information confirmed the origin of the families/flocks known from the breed history. Ninety-four percent of the samples belonged to the ovine haplogroup B (in 42 cases with full matches with the reference of GenBank, DQ852175.1). This fact proves the common maternal origin of the Hungarian Tsigai and the European sheep. A more intense focusing on the maternal side is motivated also by that the females are present at greater number than the males and they remain in breeding for a longer period of time, so they can be the depositaries of realization and maintenance of genetic diversity at a larger extent.